2008
DOI: 10.1016/j.str.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The Human Formin FHOD1 Contains a Bipartite Structure of FH3 and GTPase-Binding Domains Required for Activation

Abstract: Formins induce the nucleation and polymerization of unbranched actin filaments. They share three homology domains required for profilin binding, actin polymerization, and regulation. Diaphanous-related formins (DRFs) are activated by GTPases of the Rho/Rac family, whose interaction with the N-terminal formin domain is thought to displace a C-terminal Diaphanous-autoregulatory domain (DAD). We have determined the structure of the N-terminal domains of FHOD1 consisting of a GTPase-binding domain (GBD) and the DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 61 publications
4
73
0
Order By: Relevance
“…The often observed low affinity association of effector GBDs with GTPases precluded the direct detection of FHOD1-GTPase interactions. Expression of the active form of certain Rac-GTPases resulted, however, in pronounced recruitment to the plasma membrane (8).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The often observed low affinity association of effector GBDs with GTPases precluded the direct detection of FHOD1-GTPase interactions. Expression of the active form of certain Rac-GTPases resulted, however, in pronounced recruitment to the plasma membrane (8).…”
Section: Resultsmentioning
confidence: 98%
“…1E and supplemental Fig. S3A) (8). The amino acid sequence of the ForC ␤1-␤2 loop is very different (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,43 Instead, the major role of the RBD in FHOD1 appears to position this formin at the membrane where it will be fully activated by an unknown mechanism. This is also partly true for the formin Dia, where only a partial release of autoinhibition is seen with GTPase binding.…”
Section: Elmo Proteins In the Dock180/ Rac Pathwaymentioning
confidence: 99%
“…Release of the formin DID/DAD connection is proposed to come in the form of GTPase-binding to the formin's GTPase-binding region, although some recent data highlight that such interactions may only lead to partial release of autoinhibition (i.e., RhoAbinding to Dia1), 36,37 or not at all (i.e., Rac1-GTP engaging to FHOD1). 38 In the case of ELMO proteins, Katoh and colleagues had previously identified a RhoG-binding activity in a region flanking the DID domain, 19 therefore suggesting that ELMO activation state may be regulated by engaging small GTPase(s) much like in formins. We found that the RhoG-binding site in ELMO structurally resembles the RBD of FHOD1 but not the GBD of Dia1.…”
Section: Elmo Proteins In the Dock180/ Rac Pathwaymentioning
confidence: 99%